Opportunities And Challenges Of Majelis Zikir Dan Selawat On Becoming Indigenous Spiritual-Based Psychotherapy - Saifuddin, Ahmad (ANFUSINA: Journal of Psychology, 2022)
Majelis zikir dan selawat (MZS) is a community with a routine in the form of recitation of zikir or selawat. In the context of Indonesian culture, MZS thrives with various variants. This study seeks to uncover the opportunities and challenges of MZS as a community that has a spiritual-indigenous therapeutic element. The research was carried out by phenomenology method. The collection of data was implemented by conducting interviews and observation. As a result, these MZS have opportunities and challenges. The opportunity is to become a means of achieving catharsis, the process of changing irrational beliefs into rational, increasing submission, fostering prejudice both to God and life, and increasing social support. This opportunity makes the MZS potentially become spiritual-indigenous psychotherapy. However, the MZS assemblies also have challenges that can threaten their functioning as psychotherapy if they are not appropriately managed. One of them is their members' comprehensive rate about the meaning of dhikr and selawat and the members' objections when they have to become the host of MZS’s.